Problem Based Learning Model for Improving Arabic Speaking Proficiency in Higher Education: نموذج التعليم على المشكلات لتحسين مهارة الكلام باللغة العربية في التعليم العالي - Nur laila; Faisol Mahmoud Adam Ibrahim; Umi Machmudah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Research on Arabic language teaching models remains largely focused on conventional approaches, while the application of innovative models such as Problem Based Learning (PBL) has received limited attention, particularly in enhancing maharah kalam (speaking skills). Yet, PBL has been proven effective in promoting active student engagement through contextual problem-solving. This study aims to evaluate the effectiveness of the PBL model in improving the Arabic speaking skills of students in the Arabic Language Education Program at the University of Muhammadiyah Bima. The research employed a one-group pretest-posttest design, with data collected through observation, interviews, and speaking proficiency tests. Data analysis was conducted using a one-sample t-test. The results revealed a significant improvement in maharah kalam after the implementation of PBL, with the t-count (71.95) considerably exceeding the critical t-table value (2.144). These findings indicate that PBL is an effective approach to teaching Arabic speaking skills at the tertiary level. The study implies the need for the development of more communicative and problem-solving-based instructional designs in Arabic language education.